(untitled) (Research, Society and Development, 2022)
The objective was to evaluate increasing doses of limestone associated with nitrogen fertilization on the agronomic characteristics and nutritional value of the maize. The experimental design was randomized blocks (DBC) in a 5x2 factorial scheme, with five levels of dolomitic limestone (0; 2; 4; 6 and 8 tons per hectare) and two doses of nitrogen fertilization (protected urea) in coverage (100 and 150 kg per hectare), with 4 repetitions. Agronomic characteristics (initial start-up and plant development, pest and disease incidence, dry matter yield per hectare, ear height, plant height, grain yield per hectare and percentage of burnt grains) and nutritional value were evaluated of the whole plant (pH of the plant, crude protein, mineral matter, neutral detergent fiber, acid detergent fiber, lignin and in vitro digestibility of the whole plant and grains in percentage of dry matter). There was no significant variation in agronomic characteristics, however, there was a change in nutritional characteristics only for lignin. For the conditions studied, increasing doses of limestone associated with nitrogen fertilization did not promote improvements in agronomic characteristics, only altering the lignin content in the nutritional value of maize. More studies should be carried out on increasing doses of limestone associated with nitrogen fertilization in maize, especially in chemically poor soils.